Frequency of Maternal Complications in Obese and Non Obese Pregnant Patients - Erum Jahan, Ifat Balouch, Shahneela Moosa Memon, Tania Naveel, Fakharunissa, Asma Jabeen (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the frequency of maternal complications in obese and non obese pregnant patients. Subject and Methods: This study comprises 82 pregnant patients during their 1st trimester of pregnancy, which were further divided into 2 groups as obese and non obese as per their body mass index BMI. Mean and standard deviation was calculated for BMI and gestational age. Frequency of post operative complications and outcomes like preeclampsia and eclampsia, gestational diabetes mellitus GDM , pre-term delivery and mode of delivery were noted. Results: The majority of patients were in age group of 26 to 35 years. Mean BMI was 33.19 ± 1.837 in obese group, while in non obese group it was 22.49 ± 1.186. No significant difference was found in terms of gestational age among both groups. There was significant difference in occurrence of postoperative complications in obese group as compared to non obese group. Conclusion: An increased BMI increases the chances of preeclampsia, eclampsia, GDM, preterm delivery and C section mode of delivery.